2020
DOI: 10.1111/jep.13512
|View full text |Cite
|
Sign up to set email alerts
|

Professional judgement in clinical practice (part 3): A better alternative to strong evidence‐based medicine

Abstract: Parts 1 and 2 in this series of three articles have shown that and how strong evidence-based medicine has neither a coherent theoretical foundation nor creditable application to clinical practice. Because of its core commitment to the discredited positivist tradition it holds both a false concept of scientific knowledge and misunderstandings concerning clinical decision-making. Strong EBM continues attempts to use flawed adjustments to recover from the unsalvageable base view. Paper three argues that a promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
(161 reference statements)
0
5
0
Order By: Relevance
“… 56 , 57 , 58 , 59 , 60 , 61 The pandemic showed the shortcomings of the dominant conception of EBM, which limits the possibilities of clinical decision‐making under conditions of uncertainty and lack of consolidated knowledge. 62 The many benefits of EBM to patients are undeniable. 61 Nevertheless, we can see a limitation of this approach here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 56 , 57 , 58 , 59 , 60 , 61 The pandemic showed the shortcomings of the dominant conception of EBM, which limits the possibilities of clinical decision‐making under conditions of uncertainty and lack of consolidated knowledge. 62 The many benefits of EBM to patients are undeniable. 61 Nevertheless, we can see a limitation of this approach here.…”
Section: Resultsmentioning
confidence: 99%
“…Based on both these clinical experiences and the scientific literature, we clearly identified a first bio‐ethical issue: the inadequacy of state‐of‐the‐art practices during the first wave 56–61 . The pandemic showed the shortcomings of the dominant conception of EBM, which limits the possibilities of clinical decision‐making under conditions of uncertainty and lack of consolidated knowledge 62 . The many benefits of EBM to patients are undeniable 61 .…”
Section: Resultsmentioning
confidence: 99%
“…FCC is the foundation for clinician–parent partnership. Our study is one of few providing insight into opportunities to improve FCC for families from historically marginalized communities, highlighting the need to understand each family's context and provide supports that meets people's needs and accounts for their challenges (Browne et al, 2012; Mugerauer, 2021; Sheldrick et al, 2021). One important step is eliciting parents' multidimensional conceptualizations of health; we found that parents' definitions broadly reflect flourishing, a popular concept focusing on social and cultural factors that are central to conceptualizations of well‐being (de Ruyter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The section includes papers on EBM but extends beyond EBM to broader philosophical discussions concerning clinical knowledge, causal reasoning, research and consent-discussing issues of person-centred care and the purpose of medicine, and challenges to clinical judgement presented by the need for virtual care, a need generated by the global pandemic. [17][18][19][20][21][22][23][24][25][26][27] The first three papers in the section [17][18][19] take up the issues that were the topic of the concluding papers in the preceding 'Humanities' section, 15,16 though in this case the author outlines the history of the EBM debate from the perspective of medical philosophy and the history of ideas. The papers provide an extremely helpful account and critical analysis of the debate over the last 30 years, concluding with arguments concerning the possibilities for future development and the relationship between EBM and complexity theory, providerpatient decision making and person-centred care.…”
Section: Judgement Explanation Knowledge and Evidencementioning
confidence: 99%